The different responses of AOA and AOB communities to irrigation systems in the semi-arid region of Northeast China - Qiang, Ruowen; Wang, Meng; Li, Qian; Li, Yingjie; Li, Cuilan; Zhang, Jinjing; Liu, Hang (Frontiers in Microbiology, 2024)
Ammonia oxidation is the rate-limiting step in nitrification and the key step in the nitrogen (N) cycle. Most soil nutrients and biological indicators are extremely sensitive to irrigation systems, from the perspective of improving soil fertility and soil ecological environment, the evaluation of different irrigation systems and suitability of selection, promote crop production and soil quality, study the influence of the soil microenvironment contribute to accurate evaluation of irrigation farmland soil health. Based on the amoA gene, the abundance and community diversity of ammonia-oxidizing archaea (AOA) and ammonia-oxidizing bacteria (AOB) and their responses to soil physicochemical factors and enzyme activities were studied in semi-arid areas of Northeast China. The study consisted of three irrigation systems: flood irrigation (FP), shallow buried drip irrigation (DI), and mulched drip irrigation (MF). The results showed that DI and MF significantly increased the contents of alkaline hydrolyzed nitrogen (AN), nitrate nitrogen (NO3–-N), soil moisture, and the activities of ammonia monooxygenase (AMO) and hydroxylamine oxidase (HAO). Compared with FP, DI significantly increased the abundance of soil AOA and AOB, while MF significantly increased the abundance of soil AOB. Irrigation systems significantly affected the community composition of ammonia-oxidizing microorganisms (AOM). Also, AN and soil moisture had the greatest influence on the community composition of AOA and AOB, respectively. The AOB community had better stability and stress resistance. Moreover, the symbiotic network of AOB in the three irrigation systems was more complex than that of AOA. Compared with FP, the AOA community under treatment DI had higher complexity and stability, maintaining the versatility and sustainability of the ecosystem, while the AOB community under treatment MF had higher transfer efficiency in terms of matter and energy. In conclusion, DI and MF were more conducive to the propagation of soil AOM in the semi-arid area of Northeast China, which can provide a scientific basis for rational irrigation and N regulation from the perspective of microbiology.